2020
DOI: 10.1155/2020/8387574
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalization of Microgroove Surfaces with Antibacterial Nanocoatings

Abstract: Objectives. To investigate the physical properties of the modified microgroove (MG) and antibacterial nanocoated surfaces. In addition, the biological interactions of the modified surfaces with human gingival fibroblasts (HGFs) and the antibacterial activity of the surfaces against Porphyromonas gingivalis were studied. Methods. The titanium nitride (TiN) and silver (Ag) coatings were deposited onto the smooth and MG surfaces using magnetron sputtering. A smooth titanium surface (Ti-S) was used as the control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Therefore, the differences in cell growth and attachment between groups were not related to their hydrophilicity. In addition to hydrophilicity, the release of metal ions may also affect cell proliferation and adhesion (Lai et al, 2020). Acid etching may generate increased immersion of copper ions that could affect cell proliferation and adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the differences in cell growth and attachment between groups were not related to their hydrophilicity. In addition to hydrophilicity, the release of metal ions may also affect cell proliferation and adhesion (Lai et al, 2020). Acid etching may generate increased immersion of copper ions that could affect cell proliferation and adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…An osteon-mimetic concentric microgrooved titanium surface (CMS) was created by photolithography with an overlying 200 nm-thick layer of titanium sputtering as previously described, , modified to include a photomask containing a pattern with 10 μm wide ridges and grooves to form concentric microgrooves. The concentric circle diameter was designed to be 200 μm at the maximum diameter to mimic the natural osteon.…”
Section: Methodsmentioning
confidence: 99%
“…Cell adhesion, polarity, morphology, and cytoskeleton characteristics can be affected by implant surface topography. Previous studies by our group 21,22 demonstrated that anisotropic microgrooved titanium surface structures (60 μm width, 10 μm depth) guided human gingival fibroblasts to align along the grooves, and promoted cell proliferation by altering the arrangement of the cytoskeleton. The phenomenon of "contact induction" means that the surface topography of a material can change the arrangement and orientation of cells, thereby affecting the function of cells.…”
Section: Effects Of Go-modified Concentric Microgrooves On Cell Viabi...mentioning
confidence: 96%
“…Generally, TiN coatings are prepared through physical vapor deposition or surface nitriding. The deposited TiN coating showed good anti-adhesion against various oral bacteria in vitro and in vivo [ 82 , 83 , 216 219 ]. To further enhance the antibacterial activity, the TiN coatings were modified via a quaternization reaction.…”
Section: Strategies To Enhance Ti-based Implant Successmentioning
confidence: 99%